Advance Care Planning: Social Isolation Matters. Issue 4 (18th December 2019) - Cudjoe, Thomas K.M.; Boyd, Cynthia M.; Wolff, Jennifer L.; Roth, David L.
Abstract : BACKGROUND: Social isolation is a risk factor for poor health that influences the well‐being older adults. OBJECTIVE: We compare advance care planning (ACP) engagement of older adults who were severely socially isolated, socially isolated, and not socially isolated. DESIGN: Cross‐sectional analysis of the 2012 National Health and Aging Trends Study (NHATS). SETTING: United States of America. PARTICIPANTS: A total of 2015 older adults (aged ≥65 years) randomly selected from a representative sample of community‐dwelling Medicare beneficiaries to participate in an ACP module as part of an annual in‐person interview. MEASUREMENTS: We classified participants in three groups: severely socially isolated, socially isolated, or not socially isolated. ACP refers to three (yes/no) questions regarding whether a participant had a: (1) prior discussion about care preferences in the case of serious illness (EOL Discussion); (2) durable power of attorney (DPOA); and (3) advance directive (AD). We performed logistic regression analyses to examine the association between social isolation and ACP. RESULTS: Approximately 23% of older adults were either severely socially isolated or socially isolated. Older adults who experienced social isolation were less likely to engage in ACP than those who were not socially isolated. In adjusted analysis, older adults who were socially isolated had lower odds of having an EOL discussion (adjusted odds ratio [AOR] = 0.65; 95% confidence interval [CI] = 0.49‐0.87) or having a DPOA (AOR = 0.71; 95% CI = 0.53‐0.96) compared to those who were not socially isolated. CONCLUSION: Social isolation is associated with lower engagement in ACP. Clinicians should identify older adults who are at risk for or experience social isolation as they may benefit from targeted ACP efforts. J Am Geriatr Soc 68:841–846, 2020